STUDY OF THE EFFECT OF WATER USER FARMERS ASSOCIATION ORGANIZATION BEHAVIOR ON MANAGEMENT OF IRRIGATION NETWORK (CASE STUDY:WEST CISADANE SUB DI) - Wamindari, Indar
West Cisadane is one of the strategic irrigation location because it is near city. Of the 9 (nine) secondary channels, only 4 (four) secondary channels have water management organizations with different irrigation network conditions. It cannot be denied that the behavior of the organization can affect the result of irrigation network management. Therefore, research is needed to investigate the extent of the influence of Water User Farmers Association (P3A) organization behavior on the management of the irrigation networks. This study took 2 (two) objects, namely P3A Suka Karya which manages Nibung channels and P3A Karya Tani which manages Pagadengan channels. The purpose of this study is to determine the extent to which P3A organizational behavior can have a positive effect on the management of irrigation networks in the West Cisadane Irrigation Sub-Region. Independent variables were set in this study, which consists of 3 variables, namely motivation [X1], leadership [X2], and communication [X3], while the dependent variable is Irrigation management [Y]. The method used is quantitative research with 60 respondents who are members of 2 (two) P3A. The analyses used are statistical analysis (validity, reliability, correlation and regression test) using IBM SPSS 20.0 program. Simultaneous test results were carried out on both P3A and it was found that the variables of motivation, leadership and communication had a significant influence on the management of irrigation networks in both P3A. The result of the partial determination test shows that in both P3A Suka Karya and P3A Karya Tani, motivation has the greatest influence on the management of Irrigation networks, that are 40.88% and 35.97%. The result of the simultaneous determination test shows that the influence of the variables of motivation, leadership and communication in P3A Suka Karya is 97.7% and in the P3A Karya Tani is 97.3%. Keywords: Organizational Behavior, Motivation, Leadership, Communication, P3A, Regression, Correlation.